Allocation of Stem Cell Alterations in Spermatogenesis of Male Rats Affected by Zymafluor and Detection of Reverse Effect of Vitamin E on Testis Histology Using Immunohistochemical Techniques - Noel, Khalida I; Al-Hamdany, Muna Z; Akkila, Sameh S; Khamees , Nibras H (Scripta Medica, 2026)
Background/Aim: Zymafluor is a proven protective agent against dental caries and it is a naturally occurring agent present in water and soil. Aim of this study was to analyse the detrimental effect of sodium fluoride and opposing effect of vitamin E on spermatogenesis on testicular tissue of male rats using stem cell markers (aldehydes dehydrogenase 1A1 - ALDH1A1 and NANOG).Methods: Four groups of male rats (10 rats in each) were used in this study as follow: group C regarded as a control group received normal saline, group F received sodium fluoride (Zymafluor) once daily, group FE received vitamin E followed by sodium fluoride and group E received vitamin E. The experiment was carried out for 28 days. After this period, the rats were sacrificed and the tissue of testis was processed for immunohistochemistry to stain with ALDH1A1 and NANOG stem cell biomarkers.Results: A decrease in the expression of both ALDH1A1 and NANOG stem cell markers in group F was highly observed and statistically significant. The expression was improved in spermatic cells of group FE for both markers. Normally strong intensity of markers was observed in group E. The spermatogenesis was diminished in F group according to Jonhson score and improved in group FE, while group C and E displayed normal Johnson score for spermatogenesis.Conclusion: Sodium fluoride had a toxic effect on testis affecting spermatogenesis and decreasing quality and quantity of mature sperm, but the administration of vitamin E reversed the toxic effect of sodium fluoride, acting as an antidot. ALDH1A1 and NANOG appeared as markers of stem cell expressed in spermatogenic niche and spermatocytes and affected by many chemicals destroying these cells such as sodium fluoride.
Keywords: Zymafluor; Spermatogenesis; Testis; ALDH1A1; NANOG